Legal Protection Bonda And Bulango Languange : In Reality And Prospect - Nggilu, Novendri; Badu, Lisnawaty Wadju; Imran, Suwitno Yutye (Jambura Law Review, 2021)
72 years independent of Indonesia, the regulation of culture became a "fragmented norm" into various laws, then in 2017 Indonesia has a special law regulating the promotion of culture, as if it was an oasis in the midst of "extinction" the protection against extinct regional languages including Bonda and Bulango languages. This research is intended to examine the prospects of the policies that need to be taken by the Bone Bolango District Government in protecting and sustaining the Bonda and Bulango languages as a form of fulfillment Indonesia Constitution promises that are leerplicht. The scientific method used in this study is a type of normative research with a statute approach, case aproach and conseptual approach. The results showed that the reality of the protection of Bonda and Bulango Languages was far from the maximum word, it can be seen from the lack of documentation about the Bulango Language morphology and the condition of the use of Bulango language which only leaves one speaker, while Bonda Language is even a Bonda dictionary but its use is still limited to the Suwawa peoples only, with the condition of its speakers diminishing. The policy prospects that can be carried out by the local government in protecting and preserving the Bonda and Bulango languages include the establishment of a regional regulation on the protection and preservation of Bonda and Bulango as the basis for the Bone Bolango district Government which will regulate the obligations of educational institutions both formal and informal Primary and Secondary level in the protection and preservation of Bulango and Bonda languages, village government obligations, peoples obligations, and the role of the council of custom or duango lo lipu, including the source of the budget for the protection and preservation of Bonda and Bulango languages, and followed by technical policies others as a real form of preservation of the two languages.